A Study Of Flow Characteristics At Stilling Basin Of Tawau Dam Spillway, Sabah - Hassan, Siti Amirah Abu (Universiti Sains Malaysia, 2019)
The dam has a multi of functions, and it is not only built for power generation, but also a flood mitigation purposes. Flowing water should be controlled so that it can reduce the impact on the downstream area. The main objective of this study is to determine the velocity and to positioning of baffle blocks in stilling basin to reduce hydraulic jumps in Tawau Dam spillway model. The physical model of the Tawau Dam spillway was produced by scale 1:30 using perspex so that the characteristic of the flow could be visualized. The equipment used during this study are 'Nixon Streamflow Meter Velocity' and ‘Ultrasonic Flow Meter'. The 'Nixon Streamflow Meter Velocity' is used to measure the velocity of water at each point in the spillway and stilling basin while the 'Ultrasonic Flow Meter' is used to measure the flow rate of supply water to the model. To determine the accuracy of the equipment, the equipment had be ensure reliable set of calibration done data. Through an intensive observation, the flow characteristics in the spillway and stilling basin had been determined. Several graph had been plotted and velocity, pressure and water profile in the spillway as well as in the stilling basin. The study observed two cases of 50 L/s which is equalized to 246.5 m³/s and 100 L/s is 493.0 m³/s. From this study, it can be concluded that the characteristic of flows are depend on the amount of discharges. Therefore, to design baffle blocks for hydraulics jumps, the maximum expected flow should be determined and observed it characteristics.